Association of COL1A1 polymorphism with subchondral bone degeneration of the temporomandibular joint. Issue 12 (December 2016) - Luo, S.; Long, X.; Deng, M.; Meng, Q.; Ke, J.; Guo, H.
Abstract: The G/T polymorphism of the COL1A1 gene exhibits a clinically significant influence on bone remodelling, leading to a predisposition to degenerative diseases. The enhancement of bone turnover and further loss of bone mass are thought to be the primary pathological changes in the early degenerative course of temporomandibular joint osteoarthritis (TMJ OA), with the appearance of low-density lesions. Thus, it was hypothesized that this polymorphism may also affect this type of bone lesion in TMJ OA. A total of 130 TMJ OA patients with low-density lesions (cortical bone erosion, condylar head resorption, cyst-like lesion) and 186 healthy individuals were recruited. DNA samples were extracted from buccal mucosa swabs; genotyping was performed by high-resolution melting assay. The distribution of genotypes in these groups was compared using a multivariate logistic regression model. No significant differences in the distributions of TT and TG genotypes were observed between the groups ( P  > 0.05). Significance was detected for GG homozygous carriers ( P  = 0.043); this genotype might be a risk factor for this type of low-density lesion (odds ratio 1.643, 95% confidence interval 1.016–2.658). This study indicates that the GG genotype might be a risk factor for low-density lesions in the TMJ.